The impact of home confinement by COVID-19 on mood state and adaptive behaviors in Spanish swimmers - Jaenes, J. C.; Rubio, D. A.; Arenilla-Villalba, M. J.; Wilczynska, D. (Baltic Journal of Health and Physical Activity, 2023)
Introduction This study aimed to assess the mental condition of aquatic athletes during COVID-19 lockdowns and identify factors that could predict changes in their emotions and mood disturbances.